2018
DOI: 10.1063/1.5037598
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer process for carbon-related center in semi-insulating carbon-doped GaN

Abstract: Electron paramagnetic resonance (EPR) spectroscopy was used to study the point defects in 2 × 1017–1019 cm−3 C-doped GaN substrates grown by hydride vapor phase epitaxy. The intensity of an isotropic signal with g = 1.987 ± 0.001 increased monotonically with the carbon concentration, indicating that the EPR signal represents a carbon-related defect. In each sample, the signal intensity increased under illumination with photon energy greater than 2.75 eV, and the photo-induced signal decreased with subsequent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…In a similar fashion, Zvanut and coworkers recently identified a carbon‐related EPR spectrum in HVPE GaN substrates by comparing the spin density with SIMS measured carbon concentration in the range of 2 × 10 17 –10 19 cm −3 . Further studies showed that the defect may be photo‐excited between 2.7 and 3.4 eV and photo‐quenched between 0.9 and 2.5 eV in all the samples . In the work presented here, we use photo‐EPR to develop a model for the excitation process by directly probing two defects centers, the carbon‐related acceptor and shallow donor.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In a similar fashion, Zvanut and coworkers recently identified a carbon‐related EPR spectrum in HVPE GaN substrates by comparing the spin density with SIMS measured carbon concentration in the range of 2 × 10 17 –10 19 cm −3 . Further studies showed that the defect may be photo‐excited between 2.7 and 3.4 eV and photo‐quenched between 0.9 and 2.5 eV in all the samples . In the work presented here, we use photo‐EPR to develop a model for the excitation process by directly probing two defects centers, the carbon‐related acceptor and shallow donor.…”
Section: Introductionmentioning
confidence: 73%
“…While the spectra of Figure are dominated by a single defect, those of Figure represent two or three different centers, only one of which is the 1.987 signal. Preliminary analysis of the photo‐induced behavior was presented in earlier publications …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several research groups have published theoretical and experimental results on C-related complexes in C-doped GaN with different C doping concentrations. [17][18][19] However, the relationship between C-related defects and their electronic properties is still poorly understood in highly C-doped GaN crystal.…”
Section: Introductionmentioning
confidence: 99%
“…, 表现为深层受体 [76] ; C 掺杂浓度过 量后, GaN 中形成了大量的 Ga 位 C(C Ga )作为供体, 补偿 C N , 从而降低深层受体的浓度 [77][78] 。C N 在 2.2 eV 附近产生黄色发光带, 在 2.9 eV 附近产生蓝 色发光带(C N 跃迁发光过程见图 9(c)) [79][80] 。C 掺杂 虽然会产生与掺杂浓度相关的缺陷 [81] (见图 9(d)), 但不会对 GaN 晶体的应力和位错增值产生影响, 即 使 C 杂质浓度超过 1×10 19 cm -3 , GaN 材料也能保持 良好的晶体质量 [8] , 适度的碳掺杂甚至可能通过更 无 机 材 料 学 报 第 38 卷 图 9 C 掺杂 GaN Fig. 9 C-doped GaN (a) Formation energy versus Fermi level for C Ga and C N in GaN: Ga-rich conditions (left), and N-rich conditions (right) [79] ; (b) C N impurity model in GaN [79] ; (c) Optical transitions of C N in GaN [79] ; (d) Defect density as a function of C concentration [81] ; (e) Temperature-dependent resistivity for C doped GaN [82] ; (f) Concentrations of carbon, oxygen, and silicon in C-doped GaN layers versus the input mole fraction of pentane [82] 强地降低边缘位错密度来提高晶体质量 [82] 。通过控 制 C 前驱体的输入分压调控 C 掺杂浓度可以获得高 达 10 10 Ω•cm 的室温电阻率(图 9(e, f))。 此外, 有详细 的光电离光谱学研究表明, C 杂质与 HEMT 设备中的 陷阱中心相关, 会导致设备的电流崩塌 [83] , C N 作为 一个深层受体补偿 n 型背景杂质, 抑制高电场下的 泄漏电流, 从而提高击穿电压; 当掺杂浓度过高时, 深能级受体对 n 型背景杂质的补偿受到 C Ga -C N 自补 偿效应的抑制, 进而降低击穿电压 [77,84] 。 2021 年上海理工大学的赖云和镓特半导体科 技有限公司的 Luo 等 [85] 利用 HVPE 以浓度为 5%的 甲烷气体为掺杂源, 成功制备了 4 英寸高质量自支 撑半绝缘 GaN 晶圆片, 位错密度低于 10 6 cm -2 , 电 阻率>10 9 Ω•cm。Lyons 等 [86]…”
unclassified